What's in a Word: Observing the Contribution of Underlying and Surface Representations. (December 2017) - Chien, Yu-Fu; Sereno, Joan A.; Zhang, Jie
Abstract underlying representations play a crucial role in capturing predictable relations among different phonetic categories in phonological theory. Tone sandhi is a tonal alternation phenomenon in which a tone changes to a different tone in certain phonological environments. This study investigates whether Taiwanese listeners are more sensitive to the surface form of the tones or the underlying tonal representations of tone sandhi words. An auditory lexical decision experiment was conducted to examine priming effects between monosyllabic primes and disyllabic target words (tone sandhi T51 → T55 and sandhi T24 → T33). Each target was preceded by either a surface-tone prime (e.g., ping55-ping55tsun24; pue33-pue33jong51), an underlying-tone prime (e.g., ping51-ping55tsun24; pue24-pue33jong51), or an unrelated control (e.g., ping21-ping55tsun24; pue21-pue33jong51). Results showed significant differences in the natue of the priming effects across the two sandhi types, with productivity of the tone sandhi rule influencing how listeners' process and represent tone sandhi words.